Resolution of Fetal Hydrops in a Case of Congenital Pulmonary Airway Malformation - J. Hill, Alexandria; Clarizio, Katharine; Verma, Neelam (Journal of Fetal Surgery, 2018)
Congenital pulmonary airway malformation (CPAM) can often be noted on fetal ultrasound. When a CPAM is noted in the face of fetal hydrops, the outcome is dismal. Surgical interventions and administration of antenatal steroids can be considered for treatment, but in hydropic fetuses these interventions are not always successful. We present a case of CPAM with severe fetal hydrops that underwent steroid administration and multiple intrauterine surgical interventions, which resulted in an excellent neonatal outcome.
Keywords: Congenital pulmonary airway malformation; thoracoamniotic shunt; hydrops; cystic adenomatoid malformations; volume to head circumference ratio; intrauterine surgical intervention